Analisis Kesesuaian dan Daya Dukung Kawasan Wisata Pantai Hamadi Kota Jayapura - Aldia Rante Limbong; John Dominggus Kalor; Baigo Hamuna (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Hamadi Beach is one of the beaches that is quite popular among the Jayapura community. However, there is no data and information or adequate scientific studies regarding the level of suitability of the area and carrying capacity of the environment so that it is feared that it can affect the comfort and safety of visitors, which is actually a reference in the management and development of a tourist area, so that sustainability is also constant maintained and can be sustainable. The purpose of the study was to determine the level of suitability of the Hamadi Beach area as a tourist location at Jayapura City and find out the carrying capacity of the Hamadi Beach Tourism Area. The research was conducted in December 2018 to May 2019 in the coastal tourism area of Hamadi, Tobati Village, South Jayapura District, Jayapura City, Papua Province. The method used is the method of observation and literature. The results obtained from the study showed that the suitability level of the Hamadi Beach area as a tourist location in Jayapura City with the tourist suitability index at station 1 was 91.43% (S1 category or highly suitable), station 2 was 91.43% (S1 category or highly suitable) and station 3 is 74.29% (S2 category or suitable), with the average suitability value of all stations is 85.72% classified as S1 category or highly suitable. The carrying capacity of the Hamadi Beach Tourism Area is 9,117 people/day, of which 5,736 people/day for swimming activities and 3,381/day for beach recreation activities.Key Words: Suitability; Carrying capacity; Recreation; Hamadi beach